Pravno urejanje življenskega ! okolja - Igličar, Albin (Teorija in praksa, 2011)
Judicial rules differ from other types of social norms not only by the importance of the relationships they govern, but also by the organised sanctions they enforce and their organised formation. This allows for a higher degree of certainty that judicial rules are rational and that people will conform to them. This is why judicial rules are the preferred manner of governing social attitudes, namely those social relations which are vitally important in society. The regulations issued by Slovenian communes are formed through a pre-determined process in statutory and legally determined governing bodies. Such regulations also define sanctions and the bodies responsible for enforcing the said sanctions when communal regulations are violated. Alongside general judicial rules in by-laws, municipal administrative bodies also pass a multitude of decisions and resolutions in which specific individual judicial rules are included. Apart from the legal sphere, certain local environments also give rise to customs, traditions and moral norms which further elaborate and add value to the system of judicial rules and legal norms. These social norms which operate parallel to the law are formed spontaneously over longer periods of time and are slowly adopt them as mandatory commandments. Often a part of such a set of rules is gathered together and shaped into a well-rounded system of behaviour or a code of behaviour which is obeyed by certain categories of local residents or the local community's employees.
Keywords: Law; Pravo; Legal norms; Pravne norme; Local communities; Lokalne skupnosti; Dwelling environment; Bivalno okolje; Družbeni odnosi; Social relations